A versatile three-dimensional foam fabrication strategy for soft and hard tissue engineering. (8th February 2018) - Xu, Changlu; Bai, Yanjie; Yang, Shaofeng; Yang, Huilin; Stout, David A; Tran, Phong A; Yang, Lei
Abstract: The fabrication strategies of three-dimensional porous biomaterials have been extensively studied and well established in the past few decades, yet the biocompatibility and versatility of porous architecture preparation is still lacking. Herewith, we present a novel and green 3D porous foam fabrication technique for both soft and hard engineering. By utilizing the gelatinization and retrogradation properties of starches, stabilized porous constructs made of various building blocks, from living cells to ceramic particles, were created for the first time. In soft tissue engineering applications, 3D cultured tissue foam (CTF) with controlled cell release properties was developed, and foams constituting osteoblasts, fibroblasts and vascular endothelial cells all exhibited high mechanical stability and preservation of cell viability or functions. More importantly, the CTF achieved sustained self-release of cells controlled by serum concentration (containing amylase) and the released cells also maintained high viability and functions. In the context of hard tissue engineering applications, ceramic/bioglass (BG) foam scaffolds were developed by a similar starch-assisted foaming strategy where the resultant bone scaffolds of hydroxyapatite (HA)/BG and Si3 N4 /BG possessed >70% porosity with interconnected macropores (sizes 200 ∼ 400 μ m), fine pores (sizes 1 ∼ 10 μ m) and superior mechanical properties despite the high porosity. Additionally, in vitro and in vivo evaluations of the biological properties revealed that porous HA/BG foam exhibits the desired biocompatibility and osteogenesis. The in vivo study indicated new bone ingrowth after 1 week and significant increases in new bone volume after 2 weeks. In conclusion, the presented foaming strategy provides opportunities for biofabricating CTF with different cells for different target soft tissues and preparing porous ceramic/BG foams with different material components and high strengths, showing great versatility in soft and hard tissue engineering.